An enzyme–inorganic hybrid nanoflower based immobilized enzyme reactor with enhanced enzymatic activity. Issue 11 (13th February 2015) - Yin, Yuqing; Xiao, Yun; Lin, Guo; Xiao, Qi; Lin, Zian; Cai, Zongwei
Abstract : Ca3 (PO4 )2 –ChT hybrid nanoflowers were synthesized by a facile approach. The nanoflowers exhibited an enhanced enzymatic activity and can be used as an immobilized enzyme reactor (IMER) for highly efficient protein digestion. Abstract : A facile approach for the synthesis of enzyme–inorganic hybrid nanoflowers and their application as an immobilized α-chymotrypsin (ChT) reactor (IMER) for highly efficient protein digestion was described. The hybrid nanoflowers were room-temperature synthesized in aqueous solution using calcium phosphate (Ca3 (PO4 )2 ) as the inorganic component and ChT as the organic component. The effects of reaction parameters on the formation of the enzyme-embedded hybrid nanoflowers and their growth mechanism were investigated systematically. By monitoring the reaction of N -benzoyl-l -tyrosine ethyl ester (BTEE), the enzymatic activity of the immobilized ChT was calculated and the results showed 266% enhancement in enzymatic activity. The performance of such a nanoreactor was further demonstrated by digesting bovine serum albumin (BSA) and human serum albumin (HSA), with a stringent threshold for unambiguous identification of these digests, the yielding sequence coverages for nanoflower-based digestion were 48% and 34%, higher than those obtained with the free enzyme. The digestion time of BSA and HSA in the former case was less than 2 min, about 1/360 of that performed in the latter case (12 h). Furthermore, the residual activity of the nanoflowers decreased slightly even after eight repeated use, demonstrating promising stability. In addition, the hybrid nanoflower-based IMER was applicable to the digestion of a complex human sample, showing great promise for proteome analysis.